Functional and patient‐reported changes in swallowing and voice after combined chemotherapy and radiotherapy for limited‐stage small‐cell lung cancer. Issue 6 (21st July 2021) - Frowen, Jacqui; Gough, Karla; Hughes, Rhys; Drosdowsky, Allison; Duffy, Mary; Kiss, Nicole; Phipps‐Nelson, Jo; Siva, Shankar; Solomon, Benjamin; Ball, David
Abstract: Introduction: The purpose of this study was to describe the nature and impact of dysphagia and dysphonia in patients with limited‐stage small‐cell lung cancer (SCLC) before and after chemoradiation. Methods: A prospective cohort study was conducted on patients receiving chemoradiotherapy for limited‐stage SCLC. Patients received either 40, 45 or 50 Gy, commencing the second cycle of chemotherapy. Outcomes included: videofluoroscopy (VFSS) to investigate aspiration, swallowing function and oesophageal motility; oral intake limitations; patient‐reported dysphagia; and patient‐reported dysphonia. Data were collected before treatment and one, three and six months post‐treatment. Results: Twelve patients were enrolled. Oropharyngeal swallowing was safe and functional at all times. Three patients exhibited oesophageal motility disorders before treatment, and a further three post‐treatment. Oral intake was most compromised one month post‐treatment with five patients either tube dependent or eating very limited diets. At all other times patients were eating normal or near‐normal diets. Despite normal oropharyngeal swallowing on VFSS, three patients reported moderate or severe dysphagia one month post‐treatment. Three additional patients reported moderate or severe difficulties three and six months post‐treatment. Patients who reported dysphagia one month post‐treatment all received a mean and maximum oesophageal dose of ≥15.7 Gy and ≥42 Gy, respectively. Dose–response relationships were not apparent three and six months post‐treatment. Voice problems varied, with worst scores reported one month post‐treatment. Conclusions: This study identified discordance between observed swallowing function and patient‐reported problems, which has clinical implications for patient management, and highlights future research needs. Ongoing efforts to reduce mucosal toxicity in patients with lung cancer are essential.